الأسس الأخلاقية والفَلسفية في كتاب "ثمانية فصول" لموسى بن ميمون دراسة تحليلية نقدية مقارنة - رانيا روحى محمود کامل (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd)
يُعد موسى بن ميمون المعروف باسم "רמב"ם"(رامبام) أحد أبرز الفلاسفة والعلماء اليهود في العصر الوسيط، تميزت أعماله بدمج الفلسفة الأرسطية مع التعاليم الدينية اليهودية، من بين أعماله البارزة  كتاب "ثمانية فصول" الذي يُعد مقدمة لفصل من فصول المشنا الذي ضمنها في كتابه "تفسير المشنا"وهو "فصول الآباء"، وله طابع فلسفي، ودُون الأصل بخط اليد؛ فضلا عن أسلوبه المتأثر بالعربية. وقد تأثر ابن ميمون فيه بشكل واضح بالفلاسفة اليونان مثل أرسطو، وأفلاطون، وكذلك بالفلاسفة العرب مثل الفارابي وابن رُشد، مما جعل أعماله جسرًا يربط بين الفكر الفلسفي اليوناني والتراث الإسلامي. يقدم هذا البحث دراسة "تحليلية نقدية مقارنة" للأفكار الأخلاقية والفلسفية التي تناولها ابن ميمون في كتابه، ومقارنة بعض الأفكار بين ابن ميمون وغيره من الفلاسفة.  ومدى توافقها مع القيم الأخلاقية والدينية في عصره، مُسلطين الضوء على كيفية تفاعله مع تراثه الفكري والديني، وكيف سعى لدمج الفلسفة بالدين بحذر رغم التحديات والشائعات المعادية للفلسفة في ذلك الوقت، مع استخدام التفسيرات الكتابية لإضفاء الشرعية عليها، ولتوضيح إمكانية توافق الفلسفة مع الشريعة والمساهمة في تفسيرها وتوضيحها بطريقة تحافظ على التوازن بين العقل والإيمان.Moses Maimonides, known as "Rambam", is one of the most prominent Jewish philosophers and scholars of the Middle Ages. His works were distinguished by their integration of Aristotelian philosophy with Jewish religious teachings. Among his most notable works is the book "Eight Chapters", which is considered an introduction to a chapter of the Mishnah that he included in his book "Interpretation of the Mishnah", which is "Chapters of the Fathers". It has a philosophical character, and the original was handwritten; in addition to his style influenced by Arabic. Maimonides was clearly influenced by Greek philosophers such as Aristotle and Plato, as well as Arab philosophers such as Al-Farabi and Ibn Rushd, which made his works a bridge between Greek philosophical thought and Islamic heritage.This research presents a critical analytical comparative study of the ethical and philosophical ideas that Maimonides addressed in his book, and a comparison of some ideas between Maimonides and other philosophers. And the extent of its compatibility with the moral and religious values ​​of his time, highlighting how he interacted with his intellectual and religious heritage, and how he sought to carefully integrate philosophy with religion despite the challenges and anti-philosophy rumors at the time, while using scriptural interpretations to legitimize it, and to clarify the possibility of philosophy’s compatibility with the Sharia and contribute to its interpretation and clarification in a way that maintains a balance between reason and faith.